A Thirteenth-Century Tile Kiln at North Berwick, East Lothian, and Scottish Mediaeval Ornamented Floor Tiles - Richardson, James S (Proceedings of the Society of Antiquaries of Scotland, 1929)
The kiln was discovered close to the ruined Cistercian convent. Debris within the chambers of the kiln contained broken tiles and wasters. Tiles of the type found do not occur elsewhere in Scotland. A discussion of floor tiles across Scotland is included.